Common Coding Variants in SCN10A Are Associated With the Nav1.8 Late Current and Cardiac Conduction. (May 2018) - Macri, Vincenzo; Brody, Jennifer A.; Arking, Dan E.; Hucker, William J.; Yin, Xiaoyan; Lin, Honghuang; Mills, Robert W.; Sinner, Moritz F.; Lubitz, Steven A.; Liu, Ching-Ti; Morrison, Alanna C.; Alonso, Alvaro; et al.
Abstract : Background: Genetic variants at the SCN5A / SCN10A locus are strongly associated with electrocardiographic PR and QRS intervals. While SCN5A is the canonical cardiac sodium channel gene, the role of SCN10A in cardiac conduction is less well characterized. Methods: We sequenced the SCN10A locus in 3699 European-ancestry individuals to identify variants associated with cardiac conduction, and replicated our findings in 21, 000 individuals of European ancestry. We examined association with expression in human atrial tissue. We explored the biophysical effect of variation on channel function using cellular electrophysiology. Results: We identified 2 intronic single nucleotide polymorphisms in high linkage disequilibrium ( r   2 =0.86) with each other to be the strongest signals for PR (rs10428132, β=−4.74, P =1.52×10 −14 ) and QRS intervals (rs6599251, QRS β=−0.73; P =1.2×10 −4 ), respectively. Although these variants were not associated with SCN5A or SCN10A expression in human atrial tissue (n=490), they were in high linkage disequilibrium ( r   2 ≥0.72) with a common SCN10A missense variant, rs6795970 (V1073A). In total, we identified 7 missense variants, 4 of which (I962V, P1045T, V1073A, and L1092P) were associated with cardiac conduction. These 4 missense variants cluster in the cytoplasmic linker of the second and third domains of the SCN10A protein and together form 6 common haplotypes. Using cellular electrophysiology, we found that haplotypes associated with shorter PR intervals had a significantly larger percentage of late current compared with wild-type (I962V+V1073A+L1092P, 20.2±3.3%, P =0.03, and I962V+V1073A, 22.4±0.8%, P =0.0004 versus wild-type 11.7±1.6%), and the haplotype associated with the longest PR interval had a significantly smaller late current percentage (P1045T, 6.4±1.2%, P =0.03). Conclusions: Our findings suggest an association between genetic variation in SCN10A, the late sodium current, and alterations in cardiac conduction. Abstract : Supplemental Digital Content is available in the text.